The effectiveness of using mural as teaching aid in learning elements of art in measuring the form 1 students performance achievement / Rohazlina Hassim - Hassim, Rohazlina (2013)
This study aims to identify effective use of murals as teaching aid in learning elements of art in measuring the form 1 students performance achievement. The findings obtained from the questionnaire were distributed to the students involved and the results interviews with some respondents. The method used was a quasi experiment in which pre-test and post test conducted among two groups. The group was the control group and the experimental group. Results were analyzed using SPSS. Based on the findings, the use of murals in the teaching and learning of art elements very effectively. The use of murals as teaching aids can also diversify the use of teaching aids among teachers of Visual Arts.